Prognostic impact of human papilloma virus (HPV) genotyping and HPV-16 subtyping in vaginal carcinoma - Larsson, Gabriella Lillsunde; Helenius, Gisela; Andersson, Sören; Sorbe, Bengt; Karlsson, Mats G. (Gynecologic oncology, 2013)
The objectives of this study are to investigate the human papilloma virus (HPV) distribution in vaginal cancer and to evaluate HPV-genotype as well as HPV16-variant impact on prognosis. Sixty-nine patients diagnosed with primary vaginal carcinoma (1975–2002) were included in the study. Detection of twelve high-risk HPV (hr HPV) and two low-risk HPV (lr HPV) was performed with realtime-PCR. Samples positive for HPV-16 were analyzed for variants in the E6-gene with PCR and pyrosequencing. 53.6% (37/69) of the tumors were found to be HPV-positive, mostly for HPV-16 (N=26). Other HPV-types were HPV-18 (N=2), HPV-31 (N=2), HPV-33 (N=2), HPV-45 (N=1), HPV-52 (N=2), HPV-56 (N=1) and HPV-58 (N=1). Only European subtypes of HPV-16 were represented and the two most common HPV-16-variants were E-p (N=13) and E-G350 (N=11). Patients with HPV-positive tumors (N=37) had a significantly (log-rank test=3.341; p=0.0008) superior 5-year overall survival rate as well as cancer-specific survival rate and progression-free survival rate (p=0.0002; p=0.0004), compared with patients with HPV-negative tumors (N=32). Interestingly, patients with HPV-16-positive tumors had a superior overall survival compared with patients with tumors containing other HPV-genotypes. In a Cox proportional multivariate analysis age, tumor size, and HPV-status were independent and significant prognostic factors with regard to overall survival rate. HPV-status is of prognostic importance in vaginal carcinoma and varies with viral genotype. In this era of HPV-vaccination, genotypes other than those included in the vaccination program could still lead to vaginal carcinoma with unfavorable prognosis. ► We investigate the HPV-distribution and impact on prognosis in vaginal carcinoma. ► Survival is better for patients with HPV-positive tumors. ► HPV-16 indicates better survival compared to other HPV-genotypes.